Disruption of volitional control in obsessive-compulsive disorder: Evidence from the Bereitschaftspotential. (30th August 2019) - Takashima, Shiro; Najman, Fernando Araujo; Ramos, Renato Teodoro
Highlights: The readiness potential (RP) amplitude correlates with attention to intention to act This effect was found in the late portion of the RP, in healthy participants The attention to motor intention does not affect the RP in OCD patients Volitional components of the RP seem to be attenuated in OCD Abstract: In the context of controversies involving possible abnormalities in the volition and action control in obsessive-compulsive disorder (OCD), the current study examined electroencephalographic correlates of automatic and volitional brain processes involved in the genesis of spontaneous movements in individuals diagnosed with OCD. For this, the amplitudes of early and late Bereitschaftspotential (early BP and late BP) from 12 patients and 12 controls were obtained while they performed spontaneous button presses under different levels of volitional experience. In the first condition, participants were distracted from their motor actions by a mental task (automatic condition) and in the second condition they were instructed to attending to their own intention to move (willed condition). The results corroborate previous report that the attention to (and, presumably, the awareness of) intention to act accounts for the expression of significant portion of the late BP in healthy individuals. More relevantly, the increased late BP in willed condition in relation to automatic condition was not present in the OCD group. Neither groups nor conditions affected the early BP. In sum, the current findings suggest the existence of abnormalities in the brain activities associated with the establishment of volitional control in OCD patients.